Mechanisms For Resisting The Zionist Entity And Its Allies And Thwarting Its Plans And Conspiracies: An Analytical Study From The Perspective Of Islamic Jurisprudence And Its Evidence - Muneer Ali Abdul Rab; Baidar Mohammed Mohammed Hasan; Setiyawan Bin Gunardi (HRMARS, 2025)
Non-Indexed Publication